Sequencing of serially passaged measles virus affirms its genomic stability and reveals a nonrandom distribution of consensus mutations. (13th April 2020) - Leber, Mathias Felix; Hoyler, Birgit; Prien, Stefanie; Neault, Serge; Engeland, Christine E.; Förster, Judith M.; Bossow, Sascha; Springfeld, Christoph; von Kalle, Christof; Jäger, Dirk; Bell, John C.; Ungerechts, Guy
Abstract : Oncolytic virotherapy is an emerging treatment option for numerous cancers, with several virus families currently being evaluated in clinical trials. More specifically, vaccine-strain measles virus has arisen as a promising candidate for the treatment of different tumour types in several early clinical trials. Replicating viruses, and especially RNA viruses without proofreading polymerases, can rapidly adapt to varying environments by selecting quasispecies with advantageous genetic mutations. Subsequently, these genetic alterations could potentially weaken the safety profile of virotherapy. In this study, we demonstrate that, following an extended period of virus replication in producer or cancer cell lines, the quasispecies consensus sequence of vaccine strain-derived measles virus accrues a remarkably small number of mutations throughout the nonsegmented negative-stranded RNA genome. Interestingly, we detected a nonrandom distribution of genetic alterations within the genome, with an overall decreasing frequency of mutations from the 3′ genome start to its 5′ end. Comparing the serially passaged viruses to the parental virus on producer cells, we found that the acquired consensus mutations did not drastically change viral replication kinetics or cytolytic potency. Collectively, our data corroborate the genomic stability and excellent safety profile of oncolytic measles virus, thus supporting its continued development and clinical translation as a promising viro-immunotherapeutic.